Accelerating Insight: A Thorough Systematic Review on Driving Simulators and Their Transformative Effect on Driver Behaviour - Affandi, Muhamad Aiman; Mokhtar, Nur Hazwani; Hassan, Muhammad Zahir; Paiman, Noor Faradila; Mohd Jawi, Zulhaidi; Yoshifusa, Matsuura (Journal of Advanced Research Design, 2025)
Driving simulators have emerged as a valuable tool for evaluating driver behaviour and performance in various scenarios, offering a controlled and safe environment for testing and research. In this paper, a systematic review following a Prisma guideline to assess the effectiveness of driving simulators across a range of scenarios and examine their potential applications in enhancing road safety and driver training. The review incorporates studies published between 2019 and 2023 that investigated driving simulator effectiveness. A comprehensive search was conducted across major scientific databases, resulting in a final selection of 39 relevant articles. These studies encompassed diverse scenarios, including urban driving, highway driving, adverse weather conditions, distracted driving and impaired driving, among others. Several studies have reported positive effects on driver skills, knowledge acquisition and hazard perception after simulator-based training interventions. Furthermore, simulator-based assessments and training have the potential to address specific populations, such as older drivers or individuals with certain medical conditions, by tailoring scenarios to their unique needs. However, some limitations were identified within the reviewed studies, including limited sample sizes, variations in simulator fidelity and software and potential discrepancies between simulator and real-world driving experiences.